Histopathological investigation of the effect of coenzyme q10 on intestinal mucosa and tight junction proteins in experimental colitis model - Saadet Ozen Akarca Dizakar; Murside Ayse Demirel (Eurasian Journal of Veterinary Sciences)
Aim: The purpose of this study is to investigate the effect of Coenzyme Q10 (CoQ10) on the mucosa, goblet cell density and tight junction (TJ) proteins in the acetic acid-induced colitis model in rats. Materials and Methods: Twenty-four,10-week-old female Wistar albino rats were used in the study and divided into 3 groups; Control(n=4), Colitis (n=10) and Colitis+ CoQ10 (n=10). The colitis model was induced with 4% acetic acid. One day after colitis induction, CoQ10 was administered to the Colitis+CoQ10 group by gavage (30 mg/kg/day) for 10 days. After the treatment, the sacrification of the experimental animals was carried out. The macroscopic evaluation was performed. Microscopic scoring and goblet cell density by staining sections with Masson?s Trichrome and Alcian blue; TJ proteins were also evaluated by immunohistochemical analyzes of Occludin (Occ), Zonula Ocludens-1 (ZO-1), and Claudin-1 (Cl-1). Results: Macroscopic and microscopic scoring of colon tissues belonging to the colitis group showed a statistically significant increase compared to the control group (p<0.05). In the colitis+CoQ10 group, macroscopic and histopathological damage decreased significantly (p<0.05), and the percentage of Alcian blue staining area and the goblet cell density increased statistically with CoQ10 compared to the colitis group (p<0.05). It was also noted that there was an increase in the immunoreactivity of TJ proteins, which are important in the integrity of the mucosal barrier. Conclusion: CoQ10 showed a positive effect on histopathological changes and tight junction proteins in acetic acid-induced colitis model. However, it is thought that more detailed and various experimental and clinical studies supported by advanced molecular techniques are needed on the protective effects of CoQ10 against ulcerative colitis patients.